Forecasting Sales of Salisil Talk Wangi 45 gr Using the Double Moving Average Method at PT X - Nur, Rahmi M; Riyantori, Refki; Musharyadi, Feri (Journal of Engineering Science and Technology Management (JES-TM), 2025)
PT X is a pharmaceutical manufacturing company producing cosmetics, household health supplies, medicines, and quasi-drugs. During the internship period of 8 months, various aspects of agro-industrial logistics were observed, including demand planning. The study focused on addressing recurring issues of stockouts of talcum powder, specifically Salisil Talk Wangi 45 grams, caused by inaccurate forecasting and manual estimation methods. To resolve this, the Double Moving Average method was applied to forecast demand for the product. The results showed that for the Blue variant of Salisil Talk Wangi 45 gr, the forecasting error was MAD = 1.236 and MAPE = 7%. For the Yellow variant, MAD = 1.109 and MAPE = 7%, and for the Green variant, MAD = 1.109 and MAPE = 8%. These results suggest that the Double Moving Average method is effective in supporting raw material planning for better production continuity.